Contribution of SARS-CoV-2 infection preceding COVID-19 mRNA vaccination to generation of cellular and humoral immune responses in children - Verheul, Marije K.; Vos, Martijn; de Rond, Lia; De Zeeuw-Brouwer, Mary-Lène; Nijhof, Kim H.; Smit, Debbie; Oomen, Debbie; Molenaar, Petra; Bogaard, Marjan; van Bergen, Rianne; Middelhof, Irene; Beckers, Lisa; et al. (Frontiers in Immunology, 2023)
Primary COVID-19 vaccination for children, 5-17 years of age, was offered in the Netherlands at a time when a substantial part of this population had already experienced a SARS-CoV-2 infection. While vaccination has been shown effective, underlying immune responses have not been extensively studied. We studied immune responsiveness to one and/or two doses of primary BNT162b2 mRNA vaccination and compared the humoral and cellular immune response in children with and without a preceding infection.Antibodies targeting the original SARS-CoV-2 Spike or Omicron Spike were measured by multiplex immunoassay. B-cell and T-cell responses were investigated using enzyme-linked immunosorbent spot (ELISpot) assays. The activation of CD4 + and CD8 + T cells was studied by flowcytometry.Primary vaccination induced both a humoral and cellular adaptive response in naive children. These responses were stronger in those with a history of infection prior to vaccination. A second vaccine dose did not further boost antibody levels in those who previously experienced an infection. Infectioninduced responsiveness prior to vaccination was mainly detected in CD8 + T cells, while vaccineinduced T-cell responses were mostly by CD4 + T cells.Thus, SARS-CoV-2 infection prior to vaccination enhances adaptive cellular and humoral immune responses to primary COVID-19 vaccination in children. As most children are now expected to contract infection before the age of five, the impact of infection-induced immunity in children is of high relevance. Therefore, considering natural infection as a priming immunogen that enhances subsequent vaccine-responsiveness may help decision-making on the number and timing of vaccine doses.